Death Penalty for Criminal Actions in Indonesia in a Legal Perspective and Human Rights - Suyatno Suyatno; Hudi Yusuf (Journal of Social Research, 2023)
Death penalty for perpetrators of narcotics crimes is one of the punishments that is debated in various international countries, especially in Indonesia, a very big reaction from the community and even international countries in responding and intervening in the imposition of capital punishment with various fundamental reasons that death penalty is one of the crimes. the most cruel, sadistic, and undignified. This study aims to analyze capital punishment for crimes in Indonesia from a legal and human rights perspective. The method applied in this study uses normative legal research, which is a way of writing based on an analysis of several legal principles and legal theories as well as laws and regulations that are appropriate and related to problems in legal research writing. Death penalty for perpetrators of narcotics crimes in a country based on Pancasila as the basis of the philosophy of the Indonesian state and the 1945 Constitution of the Republic of Indonesia as the Great State Norms or Basic Norms of the Unitary State of the Republic of Indonesia and certain statutory regulations that regulate them in law something positive that is upheld is not said to violate the provisions on human rights violations, especially the basic right to life which is continuously debated in various international conventions, this must continue to be implemented.